2021
DOI: 10.1109/access.2021.3108551
|View full text |Cite
|
Sign up to set email alerts
|

Associating Measles Vaccine Uptake Classification and its Underlying Factors Using an Ensemble of Machine Learning Models

Abstract: Measles is one of the significant public health issues responsible for the high mortality rate around the globe, especially for developing countries. Using nationally representative demographic and health survey data, measles vaccine utilization has been classified, and its underlying factors are identified through an ensemble Machine Learning (ML) approach. Firstly, missing values are imputed employing various approaches, and then several feature selection techniques have been applied to identify the crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Next, [27] was implemented as an example of a light weight DNN. This model uses depthwise separable CNN [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Next, [27] was implemented as an example of a light weight DNN. This model uses depthwise separable CNN [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Ozkaya et al [46] extracted deep features using VGG- , GoogleNet [47] , and ResNet- models, which were classified by Support Vector Machine (SVM) [48] with linear kernel function. They also applied the modified T-test [49] , a feature ranking algorithm, to select the features [50] for avoiding overfitting. Rajaraman et al [51] evaluated ImageNet pre-trained CNN models such as VGG- , VGG- , InceptionV 3 , Xception, Inception-ResNetV 2 , MobileNetV 2 , DenseNet- , and NasNet-mobile [52] .…”
Section: Review Of Literaturementioning
confidence: 99%
“…After the preprocessing, mainly three classification algorithms were applied: XGB, RF, and SVM. These classifiers provide improved results in many studies [ 21 , 22 , 23 ]. Furthermore, studies found significantly improved results by applying XGB in COVID-19 mortality prediction and prepared a clinically operable Covid decision support system using XGB for clinical staff [ 23 , 24 ].…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…To optimize the specified loss function, the residual will correct the previous predictor at each iteration of gradient boosting, as illustrated in Figure 3 . Regularization is applied to the loss function in order to establish the objective function in XGB, which is used to assess the model’s effectiveness [ 22 , 26 ].…”
Section: Analysis Proceduresmentioning
confidence: 99%